Hubungan Tingkat Pengetahuan dengan Sikap Ibu Hamil tentang Pandemi COVID-19 di Wilayah Kerja UPT. Kesmas Ubud I - Luh Made Mas Swandewi; Ni Nyoman Hartati; Sur Suratiah; Nengah Runiari; Dewa Made Ruspawan (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2022)
Knowledge is thoughts, understandings, ideas, concepts to make decisions and solve problems. Good knowledge will form a favorable attitude. This study aims to determine the relationship between the level of knowledge and attitudes of pregnant women about the COVID-19 pandemic in the UPT. Kesmas Ubud I,Gianyar. This research is correlational with cross sectional approach using non-probability sampling with purposive sampling technique. The population in this study were all pregnant women who used WhatsApp totaling 65 pregnant women with a sample size of 47 samples. Data in the form of primary data, namely the identity of pregnant women, knowledge of COVID-19 and attitudes of pregnant women towards COVID-19 by filling out an online questionnaire. The results showed that 44 pregnant women (93.6%) had a good level of knowledge and 42 pregnant women (89.4%) had favorable attitudes. Bivariate analysis with Spearman rank test obtained p (0.001) alpha (0.05), there is a relationship between the level of knowledge and the attitude of pregnant women about the COVID-19 pandemic in the UPT. Kesmas Ubud I, Gianyar. Researchers hope that health workers provide education to pregnant women with a sufficient level of knowledge about COVID-19.